2010
DOI: 10.1097/ijg.0b013e3181aae954
|View full text |Cite
|
Sign up to set email alerts
|

Applanation Tonometry Versus Dynamic Contour Tonometry in Eyes Treated With Latanoprost

Abstract: The fact that dIOP was significantly higher in LG, compared with NLG and CG implies that latanoprost may affect the biomechanical properties of the ocular walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 27 publications
3
29
3
Order By: Relevance
“…Recent studies have showed an established difference in IOP levels measured by DCT and GAT that varies between 0.8 and 4.9 mm Hg and exhibits, in most cases, statistically significantly higher IOP readings using the Pascal tonometer. [8][9][10][13][14][15][16][17][18][19][20][21][22][23]26,27 In the present study, DCT readings were a mean -SD of 4.3 -2.1 mm Hg higher than GAT readings (P < 0.0001), a difference that is comparable to those reported by other authors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recent studies have showed an established difference in IOP levels measured by DCT and GAT that varies between 0.8 and 4.9 mm Hg and exhibits, in most cases, statistically significantly higher IOP readings using the Pascal tonometer. [8][9][10][13][14][15][16][17][18][19][20][21][22][23]26,27 In the present study, DCT readings were a mean -SD of 4.3 -2.1 mm Hg higher than GAT readings (P < 0.0001), a difference that is comparable to those reported by other authors.…”
Section: Discussionsupporting
confidence: 92%
“…33 While investigating the effect of topical prostaglandine analogs on glaucoma and nonglaucoma subjects, Detorakis et al showed a higher DIOP in glaucoma patients treated with latanoprost in comparison to normal controls and glaucoma patients receiving other IOP-lowering medication, a finding that was attributed by the authors to possible induced alterations in the biomechanical properties of the ocular walls. 27 However, the study did not differentiate between different ocular hypotensive agents that focused mostly on the effect of latanoprost on DCT-GAT difference. In a recently published study, Wang et al investigated various factors that could affect the difference in IOP readings between DCT and GAT, reporting a positive correlation of DIOP to the axial length and a negative one to the corneal hysteresis.…”
mentioning
confidence: 99%
“…Eleven studies 110,134,141,143,144,161,163,202,203,210,215 reported varying levels of correlation (from no correlation to a correlation coefficient of 0.46 in one study 141 ) and the other three studies 123,148,189 reported results directly relating to CCT subgroups. Martinez-de-la-Casa and colleagues 189 reported the mean IOP difference between DCT and GAT as 5.5 mmHg for patients in the lowest CCT tertile (≤ 530 µm), 4.2 mmHg for mid-range CCT and 3.5 mmHg for those in the highest CCT tertile (> 565 µm).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In total, 642 reports were identified from the electronic searches as being possibly relevant. [189][190][191][192] three in each of Saudi Arabia, [193][194][195] India, [196][197][198] Portugal 106,199,200 and Greece [201][202][203] and two in Taiwan, 125,204 Israel, 205,206 the Netherlands, 207,208 Sweden 209,210 and Turkey. 211,212 One study took place in each of Austria, 126 Brazil, 213 France, 123 Ireland, 214 New Zealand, 215 Norway 216 and Denmark.…”
Section: Overviewmentioning
confidence: 99%
“…Differences in the measurements of the intraocular pressure (IOP) by different tonometry methods, such as Goldmann Applanation Tonometry (GAT) and Dynamic Contour Tonometry (DCT), have been previously detected in glaucomatous eyes under treatment with latanoprost and have been used as indicators of the biomechanical behaviour of the eye [1, 2]. Perhaps the most important determinator of the latter is ocular rigidity, corresponding to the mathematical relationship between pressure and volume changes of the eye [3, 4].…”
Section: Introductionmentioning
confidence: 99%